2017
DOI: 10.2147/bctt.s137709
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of the estrogen receptor and HER-2/neu in breast cancer from primary lesion to first and second metastatic site

Abstract: BackgroundHormone receptor and HER-2/neu discordance between the primary lesion and first metastasis has been reported. This study was performed to determine further biomarker discordance rates between the first and subsequent metastatic breast cancer lesions.MethodsWe performed a retrospective review of paired biomarkers from primary breast cancers compared to first reported and subsequent metastases from 103 patients with breast cancer. The estrogen receptor (ER), progesterone receptor (PR), and HER-2/neu st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 21 publications
(40 reference statements)
3
21
0
4
Order By: Relevance
“…The conversions were mainly losses in ER and PR expression, while the majority of HER2 conversions were gains. Overall, the discordance rates (and discordance-rate orders of the three receptors) observed in this study were similar to those in previous reports; [4][5][6] as frequently reported, losses of receptor expression exceeded the gains. 7,8 According to most studies, PR has the highest discordance rate, followed by ER and HER2.…”
Section: Discussionsupporting
confidence: 91%
“…The conversions were mainly losses in ER and PR expression, while the majority of HER2 conversions were gains. Overall, the discordance rates (and discordance-rate orders of the three receptors) observed in this study were similar to those in previous reports; [4][5][6] as frequently reported, losses of receptor expression exceeded the gains. 7,8 According to most studies, PR has the highest discordance rate, followed by ER and HER2.…”
Section: Discussionsupporting
confidence: 91%
“…According to this notion, metastatic disease evolution is associated with altering tumor biology. This concept is supported by a recent study showing that discordance continues also from the first to second metastases [ 30 ]. Interestingly, tumors in which heparanase expression was different between the primary tumor and its metastases exhibited inferior prognosis compared with tumors in which heparanase expression was stable (Figure 1B ).…”
Section: Discussionsupporting
confidence: 53%
“…The tumor subtype may switch between primary BC and metastatic cancer. 33,35,55 A change in subtype can have an impact on survival, particularly if the change is from a primary lesion to a metastatic lesion. Monitoring the biological behavior is recommended in several studies as it can exclude secondary malignancy, which might change therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies show that the tumor subtype may change between the primary BC and the metastatic cancer sites. 33,36 The brain was actually found to be one of the most common sites in which there is a receptor switch. 36 As such it is necessary that a biopsy is made of the recurrent or metastatic lesion for reassessment of biological features, to determine the subsequent treatment.…”
Section: Mri Imaging Features and Their Correlation To Bc Subtypementioning
confidence: 99%